2007
DOI: 10.1080/10862960701675291
|View full text |Cite
|
Sign up to set email alerts
|

It's Not Just about Teaching Kids to Read: Helping Preservice Teachers Acquire a Mindset for Teaching Children in Urban Communities

Abstract: This study looks at preservice teachers' attitudes toward children and teaching in an urban high-poverty community in relation to their involvement in two different literacy education experiences: one literacy course sequence addressed issues of cultural diversity with respect to this community, and the other did not explicitly address these issues. The study specifically examines preservice teachers' (a) attitudes toward children's literacy potential, (b) confidence in teaching children to read, and (c) inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
2
22
0
2
Order By: Relevance
“…Similarly, Mewborn (2001) and Dunphy (2010) noted that preservice teachers working with small groups in mathematics instruction contributed significantly to P-5 student's achievement. Downloaded by [Yale School of Medicine] at 13:00 25 July 2015 Stuart and Thurlow (2000) and Clark (2012) investigated the impact of preservice teachers on elementary mathematics students' achievement and attitudes; Lazar (2007) examined preservice teachers' attitudes toward children's literacy in high poverty urban schools. The findings from these studies suggested that preservice teachers' positive attitudes positively impacted the achievement and attitudes of the P-5 students.…”
mentioning
confidence: 99%
“…Similarly, Mewborn (2001) and Dunphy (2010) noted that preservice teachers working with small groups in mathematics instruction contributed significantly to P-5 student's achievement. Downloaded by [Yale School of Medicine] at 13:00 25 July 2015 Stuart and Thurlow (2000) and Clark (2012) investigated the impact of preservice teachers on elementary mathematics students' achievement and attitudes; Lazar (2007) examined preservice teachers' attitudes toward children's literacy in high poverty urban schools. The findings from these studies suggested that preservice teachers' positive attitudes positively impacted the achievement and attitudes of the P-5 students.…”
mentioning
confidence: 99%
“…Research in teacher education contexts strongly suggests that when preservice teachers have meaningful experiences teaching and learning in classrooms, they begin to recognize how communities and literacies are strengths to be drawn on in the curriculum (e.g., Lazar, 2007;Mosley & Zoch, 2011). Our students may initiate their tutoring work with students labeled ''struggling'' but come to understand their work as supporting a writer in telling his or her stories.…”
mentioning
confidence: 99%
“…One expectation is that teacher educators equip teachers and preservice teachers with the necessary tools to address issues of social justice and equity in their classrooms (Cochran-Smith, 2004;Marshall & Klein, 2009). Reading teacher educators (e.g., Lazar, 2007;Mosely, 2010;Dozier, Johnston, & Rogers, 2006) are responding to such expectations by developing courses and programs that help teachers ''analyze the relationship between language and power'' (Hadjioannou & Fu, 2007, p. 44) and construct knowledge about critical literacy so that their own instruction will address social injustices that are perpetrated through various information sources. In such courses, critical literacy is defined not only as a teaching method but also as a way of thinking that challenges issues of power, and promotes reflection, transformation, and action (McLaughlin & DeVoogd, 2004).…”
mentioning
confidence: 99%